MdATG18a overexpression improves basal thermotolerance in transgenic apple by decreasing damage to chloroplasts. (1st March 2020) - Huo, Liuqing; Sun, Xun; Guo, Zijian; Jia, Xin; Che, Runmin; Sun, Yiming; Zhu, Yanfei; Wang, Ping; Gong, Xiaoqing; Ma, Fengwang
Abstract: High temperature is an abiotic stress factor that threatens plant growth and development. Autophagy in response to heat stress involves the selective removal of heat-induced protein complexes. Previously, we showed that a crucial autophagy protein from apple, MdATG18a, has a positive effect on drought tolerance. In the present study, we treated transgenic apple ( Malus domestica ) plants overexpressing MdATG18a with high temperature and found that autophagy protected them from heat stress. Overexpression of MdATG18a in apple enhanced antioxidase activity and contributed to the production of increased beneficial antioxidants under heat stress. Transgenic apple plants exhibited higher photosynthetic capacity, as shown by the rate of CO2 assimilation, the maximum photochemical efficiency of photosystem II (PSII), the effective quantum yield, and the electron transport rates in photosystems I and II (PSI and PSII, respectively). We also detected elevated autophagic activity and reduced damage to chloroplasts in transgenic plants compared to WT plants. In addition, the transcriptional activities of several HSP genes were increased in transgenic apple plants. In summary, we propose that autophagy plays a critical role in basal thermotolerance in apple, primarily through a combination of enhanced antioxidant activity and reduced chloroplast damage.